An 'experimental' instrument: testing the torsion balance in Britain, Canada and Australia. Issue 1 (2nd January 2019) - Anderson, Katharine
ABSTRACT: The torsion balance, an instrument that was first developed to demonstrate the high precision of physical science in the laboratory became a different sort of demonstration instrument in its brief vogue in the 1920s. This article considers intersecting stories of acquiring and testing the torsion balance as a field instrument in Canada, Britain and Australia. It examines the purchasing trip and fieldwork of A. H. Miller of the Dominion Observatory in 1928–1931, testing conducted by the British Geological Survey in 1926–1930, and finally the Imperial Geophysical Experimental Survey of 1928–1930 in Australia. These different stories produce a kind of collective biography, illustrating well the variety of material and textual records that accrete around instruments, especially expensive ones. But the trials and travels of the torsion balance also point to large themes. By comparing the different ways an instrument becomes valuable, and to whom, these micro-histories reveal significant features of the developing identity of geophysics. They also show the interaction of different forms of scientific internationalism in the inter-war period.